Structural System and Local Cultural Wisdom in The Traditional Architecture of Kenali Lampung Which is Currently Starting to be Rare - Putri, Pipiet Arini; Titisari, Ema Yunita; Wikantiyoso, Respati (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2022)
This research takes a case study of traditional architecture in Lampung Province with the material and method used is descriptive qualitative by taking data and analyzing it deductively. The data was obtained from secondary data in the form of books, journals, and other sources related to the traditional architecture of Lampung. The analytical technique used is descriptive exploratory with the results of the analysis of the Kenali traditional house showing a broad understanding of space and adaptation to the environment. The form and system that supports the building are one of the community's efforts to complement and explore its natural and cultural potential. In terms of structure, construction, and connection system, this traditional house also has local wisdom that can be developed and can be used as an alternative for construction completion and natural disaster management to date.